w2-4w-12=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -12 and whose sum is -4.

-6,2

Write the factored form using these integers.

(w-6)(w+2)=0

(w-6)(w+2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

w-6=0

w+2=0

Set the first factor equal to 0.

w-6=0

Add 6 to both sides of the equation.

w=6

w=6

Set the next factor equal to 0.

w+2=0

Subtract 2 from both sides of the equation.

w=-2

w=-2

The final solution is all the values that make (w-6)(w+2)=0 true.

w=6,-2

Solve for w w^2-4w-12=0